Interlocking architecture-enabled ultrasensitive iontronic pressure sensor based on [BMIM]BF4-functionalized sponge - Xiaohui Guo; Xiaomeng Yao; Bing Hu; Xinran He; Hongtao Tan; Yaqi Yu; Haining Wang; Jiashu Cao; Zhiyuan Liu; Zhangling Duan; Ting-Jung Lin; Yunong Zhao (Chemical Engineering Journal, 2026)

Establishment of a Neonatal Facial Phenotype Atlas for Genetic Disease Screening in a Retrospective Chinese Cohort - Jieyi Chen; Yunqian Zhu; Bi Ze; Huihui Chen; Chuan Li; Qi Ni; Yulan Lu; Liyuan Hu; Lin Yang; Bingbing Wu; Huijun Wang; Laishuan Wang; et al. (Phenomics, 2026)

Barriers to incorporating dichotomy-based impervious surface datasets into high-resolution urban climate studies - Xinran Yu; Hua Yuan; Wenzong Dong; Wanyi Lin; Zhuo Liu; Jiayi Xiang; Haile Xue; Yongjiu Dai (Urban Climate, 2026)

CCL21/CCR7 axis regulates VEGF-D m6A modification to drive lymphangiogenesis and lymphatic metastasis in gallbladder cancer - Zhenheng Wu; Xinran Cai; Lei Jiang; Bin Lin; Wei Pan; Shengzhe Lin; Yanling Chen; Haijie Hong (Human Cell, 2026)
Gallbladder cancer (GBC), the most common malignancy of the biliary tract, exhibits a high propensity for lymphatic system invasion. However, the mechanisms underlying lymphatic metastasis in GBC remain poorly understood. Here, we demonstrate that C–C motif chemokine ligand 21 (CCL21) is significantly upregulated in GBC and positively correlates with lymphatic vessel density and lymph node metastasis. Both in vivo and in vitro experiments confirm that CCL21/CCR7 axis promotes lymphangiogenesis and lymphatic metastasis in GBC. Mechanistically, CCL21/CCR7 modulates Vascular Endothelial Growth Factor-D (VEGF-D) mRNA N6-Methyladenosine (m 6 A) modification in an AlkB homolog 5 (ALKBH5)-dependent manner, thereby regulating VEGF-D protein expression. Site-directed mutagenesis experiments reveal that m 6 A modification sites in the coding sequence (CDS) region of VEGF-D mRNA are critical for VEGF-D protein regulation. Collectively, our findings highlight that CCL21/CCR7 regulates VEGF-D expression via m 6 A modification, driving lymphatic metastasis in GBC.

Targeted metabolomics analysis for discriminating geographical origin of Chardonnay grape and wine at sub-regions in China's Ningxia: Terroir effect - Xiaofeng Yue; Yang Zhang; Xinran Bai; Bo-chen Liu; Yu-lin Fang; Yan-lun Ju (Food Research International, 2026)

Linking Mo/Fe ion conversion to green treatment of sulfonylurea pesticides in farmland drainage: Role of directed electron transfer and self-produced hydrogen peroxide - Bingkun Liu; Weijun Tian; Bingjie Huo; Xinbo Wang; Xinran Yu; Wei Bao; Ke Yang; Minghan Li; Yushan Wei; Yinming Ji; Daoqing Lin (Chemical Engineering Journal, 2026)

Surface nickel doping and boronization with island-sea effect for sustainable hydrodechlorination via a non-radical pathway - Wenjie Lin; Xinran Xiong; Wei Peng; Sai Yang; Junyue Ji; Zelong Zheng; You-an Chen; Yi-bo Hu (Journal of Environmental Chemical Engineering, 2026)

Anti-aging effects of low-molecular-weight polysaccharide PSP-1-1 from steamed Polygonatum sibiricum via gut microbiota modulation - Chen Zhang; Hongru Lin; Congmin Wei; Xue Long; Shuomeng Bai; Haotian Wu; Xinran Li; Zhou Yang; Yihuai Gao; Hongbing Wang (Carbohydrate Polymers, 2026)

Experimental investigation and modeling of coupled thermal–hydraulic responses in seasonally frozen weathered sandstone under unidirectional freezing - Wei Liu; Gaochao Lin; Zhenyu Wang; Xinran Sun (Cold Regions Science and Technology, 2026)

Predicting heavy metal impacts on soil ammonia oxidation during sludge land application: An interpretable framework integrating mechanistic models and machine learning - Jianju Li; Xinran Du; Zhiyuan Pan; Lin Si; Huawei Wang; Weihua Li; Rongxing Bian; Yingjie Sun; Liangliang Wei (Journal of Environmental Management, 2026)

Enhancing L-aspartate biosynthesis in Escherichia coli through combined pathway engineering and release of feedback inhibition - Daobin Wang; Tong Mu; Jingwen Yang; Xinran Ni; Xiyao Cheng; Jidong Liu; Ying Lin; Ning Li (Food Bioscience, 2026)

Rhododendron dauricum essential oil obtained by enzyme-assisted hydrodistillation for antibacterial application - Nan An; Gaofeng Zhang; Lin Lu; Haoyang Chen; Liuke Zhang; Gaolei Xi; Xu Zhao; Xinran Zhang; Shuai Yu; Tao Jia; Xiuhua Zhao; Lei Yang (Plant Biosystems, 2026)

A novel molluscicide: investigating the efficacy of the Penicillium aurantiocandidum Z12 strain in controlling the schistosome-transmitting snail Oncomelania hupensis - Lei Lin; Yin Xiong; Ping Long; Liyun Zhu; Yanfeng Gong; Liang Shi; Xinran Yang; Yue Chen; Qingwu Jiang; Yibiao Zhou (Molluscan Research, 2026)

Disparities in bioaccumulation of chlorinated organic pollutants in O. bartramii and seawater from the Northwest Pacific Ocean: Compound – specific mechanisms and health risks - Ci Wang; Xinran Liu; Yitong Gao; Zilan Wu; Li Zhang; Jingqian Xie; Xinyu Tian; Feng Wu; Xiaojie Dai; Bilin Liu; Tian Lin (Marine Pollution Bulletin, 2026)

Architecting asymmetrical Janus membrane for robust membrane distillation desalination with enhanced anti-fouling performance - Caihong Liu; Xiyu Xu; Xu Lin; Xiao Wang; Xinran Guo; Qiang He; Dan Song; Haiqing Chang (Water Research, 2026)

Predictive modeling of high-speed ice-structure interaction using PD-AE-LSTM - Ming He; Mengshan Xie; Yu Ao; Xinran Li; En-Fan Lin (Ocean Engineering, 2026)

The Role of HIF-1α/BNIP3 Pathway in Hippocampal Neuronal Autophagy in Epilepsy - Huimin Kuang; Youshi Meng; Xinran Qin; Kai Qian; Chi Gong; Sijun Li; Lin Zhang; Xiaohang Gan; Yuling Lu; Yuan Wu (Molecular Neurobiology, 2026)

Cyclic responses of typical seabed materials in two offshore wind farms of China - Bo Han; Xinran Yu; Zhishuai Zhang; Genqiang Peng; Mingbao Lin; Song Dai (Marine Georesources & Geotechnology, 2025)

Strip clearcutting and replanting effects on soil organic carbon, microbial necromass carbon, and microbial carbon use efficiency in Chinese fir plantations - Xinran Zhao; Huiling Zhou; Hongwei Xu; Lin Xu; Chengming You; Li Zhang; Bo Tan; Zhenfeng Xu; Han Li; Lixia Wang; Sining Liu; Xinglei Cui; et al. (Plant and Soil, 2025)

Vertical variation of E. coli O157:H7 survival in a black soil column under freeze-thaw cycles conditions - Jiawen Lu; Jinhua Ma; Guangze Lyu; Xinran Lin; Jiayang Hu; A. Mark Ibekwe; Jincai Ma (Applied Soil Ecology, 2025)

Characterization of CD8+ T Cells in large yellow croaker Larimichthys crocea and their dynamics in response to Cryptocaryon irritans infection - Guolong lai; Xinran Li; Sichang Liu; Luyang Zhao; Mengtian Xie; Li Huang; Wenxuan Zhang; Wenbing Bao; Yan Lin; Xinhua Chen; Yang Ding (Fish & Shellfish Immunology, 2025)

Protective effects of quercetin on LPS-induced liver injury in quails - Xinran Li; Shuang Yang; Lingxin Zhu; Huanni Song; Liming Lin; Changyu Cao (Toxicon, 2025)

Phenotypic and functional characterization of CD4-2+ T cells in large yellow croaker Larimichthys crocea - Xinran Li; Guolong Lai; Yan Lin; Sichang Liu; Wenbing Bao; Wenxuan Zhang; Li Huang; Guangming Shao; Shihao Chen; Yang Ding; Xinhua Chen (Fish & Shellfish Immunology, 2025)

The association between exposure to phthalates and cardiovascular disease: A comprehensive study utilizing NHANES data from 2005 to 2018 and network toxicology - Wei Gong; Hongyan Zhu; Xinran Sun; Jinxiu Zhang; Meiyun Lin; Peng Sun (Chemico-Biological Interactions, 2025)

Interaction mechanisms of sea cucumber proteins with flavor compounds: Adsorption behavior, dynamic equilibrium and structural changes - Xinran Li; Jiahui Song; Jian Jiao; Qiang Geng; Songyi Lin (Food Chemistry, 2025)

Efficient perfluorooctanoic acid degradation using by a vacuum ultraviolet-activated dithionite reduction system: Reactive species, process optimization, degradation pathways, and toxicity changes - Jinmin Su; Tao Lin; Yuchen Wang; Han Chen; Xinran Ge (Chemical Engineering Journal, 2025)

VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Haiyan Wang; Yifan Li; Qinyao Wang; Mengxia Wu; Ruiyuan Wang; Xinran Han; Lin Liu; Ting Liu; Chunmei Shi; Linlin Zhong; Hongyan Zhang; Yunjiang Cheng; et al. (Plant Science, 2025)

Muti-network active aerogel based on PVA, bacterial cellulose, and sodium alginate: Characterization, kinetics studies, and application for mutton preservation - Xi Zhou; Fangqu Wang; Yang Yu; Ruirui Guo; Xinran You; Xiaomei Xiang; Xiaojing Fan; Yabin Niu; Xuejiao Wang; Xianchao Feng; Lin Chen (Food Hydrocolloids, 2025)

Exploring the use of bacillomycin D to control citrus sour rot caused by Geotrichum citri-aurantii - Shiquan Qian; Xinrong Zhou; Lin lv; Qi Sun; Xinran Cheng; Qian Xie; Yanrui Chai; Enjie Diao (Journal of Stored Products Research, 2025)

Machine Learning-Based Partition Method for Cyclic Development Mode of Submarine Soil Martials from Offshore Wind Farms - Ben He; Mingbao Lin; Zhishuai Zhang; Bo Han; Xinran Yu (Journal of Marine Science and Engineering, 2025)
Offshore wind turbines are subjected to long-term cyclic loads, and the seabed materials surrounding the foundation are susceptible to failure, which affects the safe construction and normal operation of offshore wind turbines. The existing studies of the cyclic mechanical properties of submarine soils focus on the accumulation strain and liquefaction, and few targeted studies are conducted on the hysteresis loop under cyclic loads. Therefore, 78 representative submarine soil samples from four offshore wind farms are tested in the study, and the cyclic behaviors under different confining pressures and CSR are investigated. The experiments reveal two unique development modes and specify the critical CSR of five submarine soil martials under different testing conductions. Based on the dynamic triaxial test results, the machine learning-based partition models for cyclic development mode were established, and the discrimination accuracy of the hysteresis loop were discussed. This study found that the RF model has a better generalization ability and higher accuracy than the GBDT model in discriminating the hysteresis loop of submarine soil, the RF model has achieved a prediction accuracy of 0.96 and a recall of 0.95 on the test dataset, which provides an important theoretical basis and technical support for the design and construction of offshore wind turbines.

Effects of sterilization intensity on the flavor profile of canned Antarctic krill (Euphausia superba): Moderate vs. excessive - Peizi Sun; Songyi Lin; Xinran Li; Dongmei Li (Food Chemistry, 2025)

Global occurrence, food web transfer, and human health risks of polycyclic aromatic hydrocarbons in biota - Jingqian Xie; Ruo Lan; Li Zhang; Jun Yu; Xinran Liu; Zhiyang You; Fen Yang; Tian Lin (Science of The Total Environment, 2025)

Random Forest-Based Prediction Model for Stiffness Degradation of Offshore Wind Farm Submarine Soil - Ben He; Mingbao Lin; Xinran Yu; Zhishuai Zhang; Song Dai (Journal of Marine Science and Engineering, 2024)
Offshore wind power is a hot spot in the field of new energy, with foundation construction costs representing approximately 30% of the total investment in wind farm construction. Offshore wind turbines are subjected to long-term cyclic loads, and seabed materials are prone to causing stiffness degradation. The accurate disclosure of the mechanical properties of marine soil is critical to the safety and stability of the foundation structure of offshore wind turbines. The stiffness degradation laws of mucky clay and silt clay from offshore wind turbines were firstly investigated in the study. Experiments found that the variations in the elastic modulus presented “L-type” attenuation under small cyclic loads, and the degradation coefficient fleetingly decayed to the strength progressive line under large cyclic loads. Based on the experimental results, a random forest prediction model for the elastic modulus of the submarine soil was established, which had high prediction accuracy. The influence of testing the loading parameters of the submarine soil on the prediction results was greater than that of the soil’s physical property parameters. In criticality, the CSR had the greatest impact on the prediction results. This study provides a more efficient method for the stiffness degradation assessment of submarine soil materials in offshore wind farms.

Failure criterion of submarine completely weathered granite under cyclic loads in rock-based sea area - Song Dai; Xinran Yu; Bo Han; Zhishuang Zhang; Ben He; Mingbao Lin (Ocean Engineering, 2024)

Role of pyrochar amendment toward carbon neutrality of rice paddy field by mitigating methane emission: A global evaluation by meta-analysis - Xinran Liu; Shuai Yin; Shuhan Xu; Jian Lin; Chengming Zhang; Linkui Cao; Qingnan Chu; Zhimin Sha (Field Crops Research, 2024)

Different stages of flavor variations among canned Antarctic krill (Euphausia superba): Based on GC-IMS and PLS-DA - Peizi Sun; Songyi Lin; Xinran Li; Dongmei Li (Food Chemistry, 2024)

Dynamic water migration and flavor analysis of sea cucumber in the process of Sichuan pepper seasoning soak - Jiahui Song; Xinran Li; Pengfei Jiang; Songyi Lin (Food Chemistry, 2024)

Bearing Behavior of Large-Diameter Monopile Foundations of Offshore Wind Turbines in Weathered Residual Soil Seabeds - Ben He; Mingbao Lin; Xinran Yu; Genqiang Peng; Guoxiang Huang; Song Dai (Journal of Marine Science and Engineering, 2024)
The southeastern rock base sea area is the most abundant wind resource area, and it is also the mainstream construction site of offshore wind farms (OWFs) in China. The weathered residual soil is the main seabed component in the rock base area, which is the important bearing stratum of the offshore wind turbine foundation. Previous studies on the mechanical properties of seabed materials and bearing characteristics of the pile foundations in OWFs have mainly focused on the submarine soil-based seabed, resulting in a lack of direct reference for the construction of offshore wind power in the rocky seabed. Therefore, the mechanical properties of weathered residual soil and the bearing behaviors of monopile foundations are mainly investigated in this study. Firstly, dynamic triaxial tests are conducted on the weathered residual soil, and experiments analyze insight into the evolution law of the hysteresis curve, cumulative strain, and stiffness attenuation. Then, the horizontal loading behaviors of monopile foundations in residual soil are analyzed by numerical simulations; more critically, the service performances under wind and wave coupling loads are evaluated, which provide a direct theoretical basis for the construction and design of offshore wind turbine foundations in rock base seabeds.

Study on the adsorption and migration rule of Sichuan pepper characteristic volatile compounds during the cooking process in the sea cucumber body wall - Jiahui Song; Xinran Li; Dong Chen; Songyi Lin (Food Chemistry, 2024)

κ-Carrageenan masking bitterness perception in surimi gels containing potassium chloride-based salt substitutes: Gel properties, oral processing, and sensory evaluation - Ni He; Xinran Chen; Lin Li; Shaoyun Wang; Meijuan Lan; Yi Yuan; Zhenhui Zhang; Tongshuai Li; Xia Zhang; Xing He; Bing Li (Food Chemistry, 2024)

Boron isotopic compositions of middle Miocene to recent shallow-water carbonates from the South China Sea: Assessing diagenetic effects and implications for paleoclimate changes - Xinran Chen; Feifei Zhang; Yibo Lin; Mengchun Cao; Haizhen Wei; Changgui Xu; Caiwu Fan; Shu-zhong Shen (Global and Planetary Change, 2024)

High-performance static formation of methane hydrate in fixed bed constructed by incorporating expanded graphite into polyimide foam - Xinran Sun; Daiming Liu; Zhibing Xuan; Yongtao Zhang; Guodong Zhang; Chen Chen; Mengting Sun; Yan Lin; Jie Zhong; Fei Wang (Chemical Engineering Journal, 2024)

CD146, a therapeutic target involved in cell plasticity - Zhenzhen Wu; Yuzhe Zang; Chuyi Li; Zhiheng He; Jingyu Liu; Zhaoqi Du; Xinran Ma; Lin Jing; Hongxia Duan; Jing Feng; Xiyun Yan (Science China Life Sciences, 2024)

Effects of exopolysaccharide by Pediococcus acidilactici S1 on the gelation properties and microstructure of porcine myofibrillar protein - Peiran Lu; Lin Mei; Xinran Wang; Yating Wu; Guoguo Jin; Man Zhang (Food Hydrocolloids, 2024)

Association between Baijiu chemistry and taste change: Constituents, sensory properties, and analytical approaches - Wei Dong; Xinran Dai; Yintao Jia; Siting Ye; Caihong Shen; Miao Liu; Feng Lin; Xiaotao Sun; Yanfei Xiong; Bo Deng (Food Chemistry, 2024)

The characteristic terpenes in sea cucumber soaked in star anise solution were characterized by HS-SPME-GC–MS and PCA analysis - Xinran Li; Pengfei Jiang; Jiahui Song; Songyi Lin (Food Chemistry, 2024)

Study on the differences in flavor adsorption ability of sea cucumber each part based on HS-SPME-GC-MS - Jiahui Song; Xinran Li; Dong Chen; Songyi Lin (Food Bioscience, 2024)

Diagenetic effects on strontium isotopes in shallow-water carbonate sediments from Middle Miocene to Recent - Xinran Chen; Mengchun Cao; Thomas J. Algeo; Na Li; Guang-yi Wei; Yi-bo Lin; Hua Zhang; Lei Xiang; Youhua Zhu; Changgui Xu; Caiwei Fan; Shuzhong Shen; et al. (Chemical Geology, 2024)

An Adversarial Single-Domain Generalization Network for Fault Diagnosis of Wind Turbine Gearboxes - Xinran Wang; Chenyong Wang; Hanlin Liu; Cunyou Zhang; Zhenqiang Fu; Lin Ding; Chenzhao Bai; Hongpeng Zhang; Yi Wei (Journal of Marine Science and Engineering, 2023)
In deep learning-based fault diagnosis of the wind turbine gearbox, a commonly faced challenge is the domain shift caused by differing operational conditions. Traditional domain adaptation methods aim to learn transferable features from the source domain and apply them to the target data. However, such methods still require access to target domain data during the training process, which limits their applicability in real-time fault diagnosis. To address this issue, we introduce an adversarial single-domain generalization network (ASDGN). It relies solely on data from a single length of data acquisition in wind turbine fault diagnosis. This novel approach introduces a more flexible and efficient solution to the field of real-time fault diagnosis for wind turbines.

Genetic spectrums and clinical profiles of critically ill neonates with congenital auricular deformity in the China Neonatal Genomes Project - Feifan Xiao; Bingbing Wu; Chenbin Dong; Guoqiang Cheng; Yun Cao; Laishuan Wang; Xinran Dong; Yulan Lu; Lin Yang; Liping Chen; Long Li; Xinnian Pan; et al. (Human Genetics, 2023)

Potential causal links between long-term ambient particulate matter exposure and cerebrovascular mortality: Insights from a large cohort in southern China - Shirui Chen; Xiao Lin; Zhicheng Du; Yuqin Zhang; Lingling Zheng; Xu Ju; Tong Guo; Xinran Wang; Lichang Chen; Jie Jiang; Weihua Hu; Wangjian Zhang; et al. (Environmental Pollution, 2023)

Substantial short- and long-term health effect due to PM2.5 and the constituents even under future emission reductions in China - Shengnan Xiang; Xiuwen Guo; Wenbin Kou; Xinran Zeng; Feifan Yan; Guangliang Liu; Yuanyuan Zhu; Yang Xie; Xiaopei Lin; Wei Han; Yang Gao (Science of The Total Environment, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

New methods based on a genetic algorithm back propagation (GABP) neural network and general regression neural network (GRNN) for predicting the occurrence of trihalomethanes in tap water - Kangle Liu; Tao Lin; Tingting Zhong; Xinran Ge; Fuchun Jiang; Xue Zhang (Science of The Total Environment, 2023)

A 13 million-year record of Li isotope compositions in island carbonates: Constraints on bulk inorganic carbonate as a global seawater Li isotope archive - Guang-Yi Wei; Feifei Zhang; Yi-Sheng Yin; Yi-Bo Lin; Philip A.E. Pogge von Strandmann; Mengchun Cao; Na Li; Guolin Xiong; Xinran Chen; Caiwei Fan; Changgui Xu; Fei Tan; et al. (Geochimica et Cosmochimica Acta, 2023)

Multiscale numerical simulation of CO2 hydrate storage using machine learning - Alan Junji Yamaguchi; Toru Sato; Takaomi Tobase; Xinran Wei; Lin Huang; Jia Zhang; Jiang Bian; Tie-Yan Liu (Fuel, 2023)

Assessment of cancer-related signaling pathways in responses to polystyrene nanoplastics via a kidney-testis microfluidic platform (KTP) - Mingming Xiao; Xinran Li; Xinlian Zhang; Xiaoxiao Duan; Houwei Lin; Sixiu Liu; Guodong Sui (Science of The Total Environment, 2023)

Atmospheric chemistry of nitrous acid and its effects on hydroxyl radical and ozone at the urban area of Beijing in early spring 2021 - Wenqian Zhang; Shengrui Tong; Deng Lin; Fangjie Li; Xinran Zhang; Lili Wang; Dongsheng Ji; Guiqian Tang; Zirui Liu; Bo Hu; Maofa Ge (Environmental Pollution, 2023)

7,8-Dihydroxyflavone attenuates the virulence of Staphylococcus aureus by inhibiting alpha-hemolysin - Nan Bian; Xiangqian Chen; Xinran Ren; Zishu Yu; Mengli Jin; Xiaoyu Chen; Chang Liu; Yanhe Luan; Lin Wei; Ying Chen; Wu Song; Yicheng Zhao; et al. (World Journal of Microbiology and Biotechnology, 2022)

Optimized trio genome sequencing (OTGS) as a first-tier genetic test in critically ill infants: practice in China - Huijun Wang; Yulan Lu; Xinran Dong; Guoping Lu; Guoqiang Cheng; Yanyan Qian; Qi Ni; Ping Zhang; Lin Yang; Bingbing Wu; Wenhao Zhou (Human Genetics, 2020)

Natural CAC chemopreventive agents from Ilex rotunda Thunb. - Yueqing Han; Lin Zhang; Wei Li; Xinran Liu; Jiao Xiao; Gang Chen; Ning Li (Journal of Natural Medicines, 2019)